Population-based study of diabetes and risk characteristics in Turkey - Results of the Turkish Diabetes Epidemiology Study (TURDEP) - (:unkn) unknown (AMER DIABETES ASSOC, 2002)
OBJECTIVES- To investigate for the first time the prevalence of diabetes and impaired glucose tolerance (IGT) nationwide in Turkey; to assess regional variations and relationships between glucose intolerance and lifestyle and physical risk factors. RESEARCH DESIGN AND METHODS- The Turkish Diabetes Epidemiology Study (TURDEP) is a cross-sectional, population-based survey that included 24,788 subjects (age 20 years, women 55%, response 85%). Glucose tolerance was classified according to World Health Organization recommendations on the basis of 2-h blood glucose values. RESULTS- Crude prevalence of diabetes was 7.2% (previously undiagnosed, 2.3%) and of IGT, 6.7% (age-standardized to world and European populations, 7.9 and 7.0%). Both were more frequent in women than men (P < 0.0001) and in those living in urban rather than rural communities (P < 0.001). Prevalence rates of hypertension and obesity were 29 and 22%, respectively. Both were more common among women than men (P < 0.0001). Prevalence of diabetes and IGT increased with rising BMI, waist-to-hip ratio (WHR), and waist girth (P < 0.0001). Multiple logistic regression analysis revealed that age, BMI, WHR, familial diabetes, and hypertension were independently associated with diabetes, age, BMI, WHR, familial diabetes, and hypertension with IGT (except for familial diabetes in women with IGT). Education was related to diabetes in men but was protective for diabetes and IGT in women. Socioeconomic status appeared to decrease the risk of IGT in men while it increased the risk in women. Smoking had a protective effect for IGT in both sexes. CONCLUSIONS- Diabetes and IGT are moderately common in Turkey by international standards. Associations with obesity and hypertension have been confirmed. Other lifestyle factors had a variable relationship with glucose tolerance.
Keywords: IMPAIRED GLUCOSE-TOLERANCE; HIGH PREVALENCE; ALCOHOL-CONSUMPTION; MELLITUS; INTOLERANCE; UZBEKISTAN; COMMUNITY; INCREASE; DISEASE; GREECE